2004
DOI: 10.1021/ac0494937
|View full text |Cite
|
Sign up to set email alerts
|

Disposable Noncompetitive Immunosensor for Free and Total Prostate-Specific Antigen Based on Capacitance Measurement

Abstract: This work reports on the successful integration of a one-step lateral flow immunoassay format and impedance detection of the specific affinity event using an electrochemical transducer coated with a pH-sensitive polymer layer. This approach was particularly applied to the development of a rapid single-use immunosensor for the sensitive detection of free and total prostate-specific antigen (f-PSA, t-PSA) tumor marker. Strips of nitrocellulose membrane were coated with appropriate antibodies to f-PSA and t-PSA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 27 publications
1
58
0
1
Order By: Relevance
“…Their robust and simple structure, their long term stability and reliability, and easy fabrication have attracted much attention from the sensor research community. Applications that have been proposed for these microelectrodes include measurement of the concentration of calcium [1], potassium [2], p(CO2) [3], pH [4], ethanol/methanol in gasoline [5], heavy metals [6], nitrate [7], urea [8][9], glucose [10], total prostate-specific antigen (PSA) [11], bacteria [12], red blood cells (hematocrit) [13], and detection of specific sequences of DNA [14]. In some applications, the measurement of a physical magnitude such as dielectric constant or conductivity of the media provides direct information of the analyte concentration [5,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their robust and simple structure, their long term stability and reliability, and easy fabrication have attracted much attention from the sensor research community. Applications that have been proposed for these microelectrodes include measurement of the concentration of calcium [1], potassium [2], p(CO2) [3], pH [4], ethanol/methanol in gasoline [5], heavy metals [6], nitrate [7], urea [8][9], glucose [10], total prostate-specific antigen (PSA) [11], bacteria [12], red blood cells (hematocrit) [13], and detection of specific sequences of DNA [14]. In some applications, the measurement of a physical magnitude such as dielectric constant or conductivity of the media provides direct information of the analyte concentration [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…In some applications, the measurement of a physical magnitude such as dielectric constant or conductivity of the media provides direct information of the analyte concentration [5,13]. In other applications, the deposition of a membrane or functional monolayer on top of the electrodes as a recognition element is necessary to obtain sensitivity and selectivity to particular species [1][2][3][4][6][7][8][9][10][11][12][13][14]. Different arrangements of electrodes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…They can be easily conjugated to biomolecules via different cross linkers and well known chemical procedures, and the reactions they catalyze can be detected either optically 6,7 or electrochemically. [8][9][10][11] In this letter, a biosensing principle is presented and tested. It consists in the generation of ions by an enzyme and the local detection of them by polycrystalline silicon interdigitated electrodes.…”
Section: Local Detection Of Enzymatic Ion Generation With Polycrystalmentioning
confidence: 99%
“…30,31 The measurement principle using EIS is to measure the capacitance on a color line using the modified electrodes with polymer layers. 32,33 However, both methods using CA and EIS are costly because they need additional factors such as enzymes, mediators or polymers in addition to electrodes. On the other hand, a study to quantitate IST only with electrodes has been reported.…”
Section: Introductionmentioning
confidence: 99%